Use of protocol with prolonged proestrus with and without eCG in dual purpose dairy Holsteins cows in the Ecuadorian Amazons - Manuel Ortega-Coello (SPERMOVA, 2020)
The objective was to evaluate the effect of eCG on presence estrus, ovulation time, preovulatory follicle diameter and pregnancy rate in Holstein cows treated with a prolonged proestrus protocol in the Ecuadorian Amazon. The project was developed of the Province of Pastaza - Ecuador, from October 2018 to October 2019. The study used 306 Holstein multiparous dairy cows were used, milked once a day producing with an average production of 8 liters of milk per cow / day. Four treatments were used, the cows were artificially inseminated at fixed time on day nine T1: J - Synch + eCG + estrus FTAI 60 hours (n = 92); T2: J - Synch + eCG + without estrus + GnRH FTAI 72 hours (n=61), T3: J - Synch + estrus FTAI 60 hours (n = 70); T4: J - Synch + without estrus + GnRH + FTAI 72 hours (n = 83). The pregnancy rate was 59.8% (T1), 54.1% (T2), 47.1% (T3) and 41.0% (T4). Follicular development and corpus luteum diameter showed significant differences (p≤0.05). For this group of cows and with the production system used, any of the evaluated treatments could be manipulated interchangeably. Although, the J-Synch treatment with eCG and IA 60 hours would show a trend of better pregnancy rate.